RNAi Pathway Genes Are Resistant to Small RNA Mediated Gene Silencing in the Protozoan Parasite Entamoeba histolytica - Pompey, Justine M. (Public Library of Science, 2014)

(untitled)
The RNA interference pathway in the protist Entamoeba histolytica plays important roles in permanent gene silencing as well as in the regulation of virulence determinants. Recently, a novel RNA interference (RNAi)-based silencing technique was developed in this parasite that uses a gene endogenously silenced by small RNAs as a “trigger” to induce silencing of other genes that are fused to it. Fusion to a trigger gene induces the production of gene-specific antisense small RNAs, resulting in robust and permanent silencing of the cognate gene. This approach has silenced multiple genes including those involved in virulence and transcriptional regulation. We now demonstrate that all tested genes of the amebic RNAi pathway are unable to be silenced using the trigger approach, including Argonaute genes (Ago2-1, Ago2-2, and Ago2-3), RNaseIII, and RNA-dependent RNA polymerase (RdRP). In all situations (except for RdRP), fusion to a trigger successfully induces production of gene-specific antisense small RNAs to the cognate gene. These small RNAs are capable of silencing a target gene in trans, indicating that they are functional; despite this, however, they cannot silence the RNAi pathway genes. Interestingly, when a trigger is fused to RdRP, small RNA induction to RdRP does not occur, a unique phenotype hinting that either RdRP is highly resistant to being a target of small RNAs or that small RNA generation may be controlled by RdRP. The inability of the small RNA pathway to silence RNAi genes in E. histolytica, despite the generation of functional small RNAs to these loci suggest that epigenetic factors may protect certain genomic loci and thus determine susceptibility to small RNA mediated silencing.